Rootstock effects on bitter pit incidence in ‘Honeycrisp’ apples are associated with changes in fruit’s cell wall chemical properties - Islam, Md Tabibul; Liu, Jianyang; Das, Protiva Rani; Singh, Amritpal; Sherif, Sherif M. (Frontiers in Plant Science, 2022)
Bitter pit (BP) is a physiological disorder of apples that often appears during or after cold storage. Despite being defined as a calcium deficiency disorder, BP is a complex process that is not only affected by the total Ca2+ content in the fruit but also by the proper cellular Ca2+ homeostasis and partitioning. Early investigations have also suggested that rootstocks could affect BP development and severity. In the present study, rootstock effects on BP development were assessed on ‘Honeycrisp’ trees that were grafted on 14 different rootstocks (B.10, G.11, G.202, G.214, G.30, G.41, G.935, G.969, M.26 EMLA, M.9, V.1, V.5, V.6, and V.7). We evaluated BP incidence at harvest, and three months after cold storage for four, and three growing seasons, respectively. BP incidence was significantly reduced in ‘Honeycrisp’ trees on B.10 compared to other rootstocks, whereas trees on V.6 showed the highest percentage of BP at harvest and after cold storage. ‘Honeycrisp’ apples were collected from three different rootstocks (B.10, G.41, and V.6) two months after cold storage and evaluated for mineral nutrient composition, Ca2+ homeostasis, and cell wall properties, e.g., pectin content, pectin de-esterification rate and pectin methylesterase (PME) activity. Water-soluble and insoluble pectin content was markedly higher in fruits from B.10 than in G.41 and V.6. We also observed increased PME enzyme activity and a greater degree of water-insoluble pectin de-esterification in ‘Honeycrisp’ apples from V.6 compared to those from B.10. A significantly higher Ca2+ was found in the fruits from B.10 than G.41 and V.6. Higher Ca2+ and lower Mg2+ levels were also observed in the cell wall and water-insoluble pectin fractions of the fruits from B.10 compared to G.41 and V.6. However, the ratio of cell wall-bound Ca2+ to total Ca2+ was lower in B.10 compared to G.41 and V.6. Together, our results indicate that the tolerance of B.10 to BP could be attributed to a reduced PME activity and lower pectin de-esterification levels, which in turn reduced the amount of Ca2+ cross-linked with pectin, and probably increased the apoplastic free calcium concentrations that is essential for maintaining cell membrane integrity and reducing BP development.